Possibilities of using Camelina sativa oil for producing biodiesel fuel - Zaleckas, Ernestas; Makarevičienė, Violeta; Sendžikienė, Eglė (Transport, 2012)
Biofuels for diesel engines are produced mainly from rapeseed oil in Lithuania and the Member States of the European Union. In order to minimise an adverse impact of biodiesel fuel on the food sector, it is necessary to look for alternative feedstocks for producing biodiesel fuel including the potential utilisation of the new kinds of oilseed crops and various fatty waste. Camelina (Camelina sativa) could be one of the kinds of such oilseed crops, and therefore the physical and chemical parameters of Camelina sativa oil and biodiesel fuel produced from this oil were determined and the conformity of quality parameters with the requirements of biofuel standard was evaluated. It was found that fatty acid methyl esters made from Camelina sativa oil had a high iodine value (164.6÷169.6 g I2 / 100 g oil), and therefore could be used as fuel for diesel engines only in the mixtures with methyl esters produced from animal fat or used for frying oil. It has been established that similar mixtures can contain 50÷60% of Camelina sativa oil methyl esters. The possibilities of increasing oxidation stability as well as improving the cold flow properties of ester mixtures were investigated. The most effective antioxidant – Ionol (optimal dosage of 500 ppm) and the most efficient depressants Wintron XC-30 (optimal dosage – 1500 ppm) and Infineum R-442 (optimal dosage – 1200 ppm) were selected. First Published Online: 30 Mar 2012